Pengaruh Karakteristik GCG Terhadap Pengungkapan CSR Perusahaan Yang Terdaftar Pada LQ45 BEI Periode 2017-2018 Menggunakan Asimetri Informasi Sebagai Variabel Intervening - Nugroho Budi Wirawan; Negina Kencono Putri (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
The purpose of this study is to analyze the character of GCG on corporate CSR disclosure in the 2017-2018 IDX LQ45, intervening variables using information asymmetry. A number of samples of 45 companies, the analytical tool used is SPSS and data analysis methods with data normality testing, heterokedasticity testing, multicollinearity testing, and multiple linear regression testing. The results of this study reveal that GCG data has no significant effect on information asymmetry. Information asymmetry has a significant influence on CSR.Keywords: GCG, asymmetry, CSR